Novel protein kinase C phosphorylated kinase inhibitor-matrine suppresses replication of hepatitis B virus via modulating the mitogen-activated protein kinase signal. Issue 2 (1st February 2022) - Zhou, Shen; Li, Yuan; Gao, Jing; Wang, Yanyan; Ma, Xinping; Ding, Hui; Li, Xiuling; Sun, Suofeng
ABSTRACT: HBV (hepatitis B virus) infection still threatens human health. Therefore, it is essential to find new effective anti-HBV compounds. Here, we identified matrine as a novel inhibitor of PKC (protein kinase C) phosphorylated kinase by screening a natural compound library. After HepG2.215 cells were treated with matrine, we carried out a phosphorylated proteomics sequence study and analyzed the prediction of related kinase expression level. In the case of HBV infection, it was found that PKC kinase mediates the activation of mitogen-activated protein kinase (MAPK) signaling pathway known as son of sevenless (SOS) activation. It was also found that PKC kinase inhibits the expression of C-X-C Motif Chemokine Ligand 8 (CXCL8) by inhibiting the activity of activating transcription factor 2/ cAMP response element binding protein (ATF2/CREB), and this effect is independent of its activated MAPK signaling pathway. Finally, Western blot was used to detect the expression of MAPK, ATF2, CREB3 phosphorylation and nonphosphorylation in matrine-treated cells and PKC-treated cells. PKC phosphorylated kinase inhibitor-matrine suppresses the replication of HBV via modulating the MAPK/ATF2 signal. Matrine is a good clinical drug to enhance the autoimmunity in the adjuvant treatment of chronic HBV infection. Graphical Abstract: uf0001